A química dos minerais: uma temática para investigar o papel da experimentação no ensino de química - Durand, Ângela Malvina (2015)
It is well known that the use of practical / experimental activity in Chemistry Teaching is very important to the construction of scientific knowledge of the students. However, studies show that the experimental teaching still needs reforms and point alternatives for this occurs, for example, through contextualized and investigative practical / experimental activities and by public policies as PIBID, which has encouraged the teacher in training to work the experimental Chemistry. In this perspective, this work uses "Minerals" as a theme to assist in Chemistry learning process, through interventions using experimental activities. This research was developed with students from technical courses integrated to the high school of a school in Santa Maria – RS, Brazil, and is structured in two parts. In the first, applied for four classes (first and third years of high school) we seek to investigate the students’ conceptions about the role of practical / experimental activities in Chemistry. The data were obtained by questionnaire and a framework was created, containing values corresponding to the goals of the questionnaire. The second part was applied to a class of 1st year, aiming to investigate the contributions of the theme "Mineral" to the learning process through different methodologies, such as investigative activities, thematic workshops and case studies, while also promoting an interdisciplinary study with Geography. The instruments, such as questionnaires and textual productions were analyzed according to the Discursive Textual Analysis, allowing to detect the perceptions of students regarding the theme "Minerals", its relation to the Chemistry and the students' previous knowledge and those constructed by them about the theme. Our results allow us to conclude that, through the theme "Minerals" and the development of different methodologies, Chemistry Teaching was favored, because it assisted in students’ cognitive construction, allowing a better relation between Chemistry and daily life.